2013
DOI: 10.2139/ssrn.2209759
|View full text |Cite
|
Sign up to set email alerts
|

Market Value of the Firms and R&D Investment: Theoretical Overview and Empirical Estimation for the Panel of Countries

Abstract: The aim of this paper is to investigate the issue of R&D investment and the market value of firms. This idea dates back from Arrow paper, later developed by Paul Romer, but in the area of economic growth. Zvi Griliches in 1979 first introduced the production function, which was later used in a vast literature from this area. In the theoretical section of this paper, Tobin's original model and Abel's (1984) model were described. These models relate Tobin's quotient with intangible assets of the company. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The extant research focuses on US and UK firms due to the salience and liquidity of their financial markets. Only a few comparative studies have examined firms in continental Europe (Hall and Oriani, 2006;Josheski and Sopova, 2013) due to the information opacity, less-developed financial markets, and limited number of listed firms in those countries (Duqui et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The extant research focuses on US and UK firms due to the salience and liquidity of their financial markets. Only a few comparative studies have examined firms in continental Europe (Hall and Oriani, 2006;Josheski and Sopova, 2013) due to the information opacity, less-developed financial markets, and limited number of listed firms in those countries (Duqui et al, 2011).…”
mentioning
confidence: 99%
“…Existing contributions are strongly focused on USA and UK firms due to the relevance and liquidity of the financial markets of these countries. There are few comparative studies (Hall and Oriani, 2006;Josheski and Sopova, 2013) for Continental European countries, as a result of the opacity of information, the less developed financial markets, and the limited number of listed firms (Duqui et al, 2011).…”
mentioning
confidence: 99%
“…R&D investment is an important source of knowledge accumulation in enterprises. Josheski and Sopova (2013) found a positive and statistically significant relationship between R&D investment and firm’s market value using European data. Similarly, Hwang et al (2013) found that higher R&D investment in IT industry coupled with high foreign ownership result in higher firm valuation.…”
Section: Literature Reviewmentioning
confidence: 89%
“…R&D intensity is used to measure innovations, and both product innovations and process innovations are considered helpful to improve the operation efficiency of firms. Research has also found that R&D intensity is positively related to firm performance (Bradley, Jarrell & Kim, 1984;Titman & Wessels, 1988;Crutchley & Hansen, 1989;McConnell & Servaes, 1990;Hermalin & Weisbach, 1991;Jensen et al, 1992;Hirschey & Weygandt, 1993;Klette, 1996;Delios & Beamish, 1999;Kotabe et al, 2002;Lu & Beamish, 2004;Bae et al, 2008;Missaka, 2015;Josheski & Sopova, 2013;Shih-Yung et. al., 2017).…”
Section: Randd Expense Ratiomentioning
confidence: 99%